Crisis en catastrofe De Nederlandse omgang met rampen in de lange negentiende eeuw - Jensen, Lotte (Amsterdam University Press, 2021)
"Historical research into disasters and disaster processing has expanded enormously in recent years. The threat of climate disasters and pandemics is raising awareness that disasters have a major impact on community development. The period 1755-1918 also saw numerous disasters that affected Dutch society, such as the Leiden gunpowder disaster of 1807, several cholera outbreaks and large-scale river floods. Volcanic eruptions and flooding were recurring phenomena in the colonies. And then there were major international disasters, such as the Lisbon earthquake of 1755 and the Spanish flu in 1918. Crisis and Catastrophe examines the influence of these catastrophes on belief in God, solidarity and charity, and local and national identity formation. Attention is also paid to the cultural representation of disasters in literature, paintings and memorial books."